Development of a monoclonal antibody-based indirect competitive immunosorbent assay for 4(5)-Methylimidazole detection in caramels. (1st March 2015) - Wu, Xin-Lan; Yu, Shu-Juan; Kang, Ke-Ren
Highlights: Hapten of 4-MI has been successfully prepared. Ic-ELISA method to test 4-MI based on monoclonal antibody has been established. The established ic-ELISA method was sensitive and specific for 4-MI detection in caramels. Abstract: In this study, an indirect competitive enzyme-linked immunoassay (ic-ELISA) based on monoclonal antibody for 4(5)-Methylimidazole (4-MI) detection was described. The artificial antigens were prepared by conjugating bovine serum albumin (BSA) or ovalbumin (OVA) with the hapten of 4-MI. And monoclonal antibody, evaluated by ic-ELISA, was obtained by immunizing BABL/c mice. After optimizing, a standard curve for ic-ELISA detection on 4-MI was obtained with the linear detection range of 0.64–20.48 mg/L. The cross-reactivity (CR) of all the structural analogues of 4-MI was less than 5.62%. The recoveries of 4-MI in caramels detection were ranged from 88.69% to 114.09%, with relative standard deviation ( n = 3) below 8.07%. The results suggested that the established ic-ELISA is promising for 4-MI commercial detection in caramels.